Changing the Army's Weapon Training Strategies to Meet Operational Requirements More Efficiently and Effectively - Crowley, James C. (RAND Corporation, 2014)
This report presents the results of a project supporting the Army's efforts to adapt its weapon training strategies to better support operational requirements and unit readiness processes, take full advantage of training technologies, and increase efficiency. It outlines directions the Army could take to improve its weapon training strategies and the processes for adapting them.